Estrategias de marketing para el fortalecimiento comercial del centro especializado en el desarrollo integral de funciones cognitivas y estimulación adecuada, Quito – Ecuador, año 2022 - Rochina Chariguaman, Jefferson David (2023)
This research begins with the description of the center specialized in the integral development of cognitive functions and adequate stimulation, the main objective for the realization of marketing strategies is to design marketing strategies for commercial strengthening, seeking to generate a larger customer base. The implementation of marketing strategies will help to grow in the market by providing a quality service for new customers, in this way it is intended to achieve the objectives set generating greater profitability for the center, for this reason it is necessary to have the support of the center's authorities for the project to be successful. The methodology used for the research work was field and descriptive, where we can visualize from different points how the center is and we will describe the situation in which the center is in order to have a great deal of information. Matrices are elaborated to know the situation of the company where a wide internal and external investigation of the center is carried out to know in what conditions it is in. Finally, strategies are elaborated that are directed to the center which help to generate a great amount of clients offering optimal and quality services, which will benefit us to have recognition in the population before the competition. Keywords: strategies, positioning, advertising, promotion, strengthening, marketing.